Dextran produced in situ as a tool to improve the quality of wheat-faba bean composite bread. (November 2018) - Wang, Yaqin; Sorvali, Päivi; Laitila, Arja; Maina, Ndegwa Henry; Coda, Rossana; Katina, Kati
Abstract: The incorporation of faba bean flour into wheat-based products is a sustainable way to obtain protein-enriched food items. However, developing breads with a higher content of faba bean flour is challenging due to the poor textural/sensory properties of the final product. A potential solution is to use hydrocolloids as structuring agents to increase the viscoelastic properties of the composite bread. Microbial dextran is a natural hydrocolloid which can be used as a bread texture improver either as a pure food ingredient or by in situ production during sourdough fermentation. The aim of this study was to compare the influence of dextran produced in situ by Weissella confusa VTT E−143403 (E3403) and Leuconostoc pseudomesenteroides DSM 20193 in faba bean sourdoughs on the quality of wheat bread supplemented with 43% faba bean sourdough. The impact of dextran on the rheological properties of dough and textural properties of the final bread were evaluated. Dextran formed by W. confusa and L. pseudomesenteroides reached a level of 5.2 and 3.6% (flour basis), respectively. Incorporation of faba bean sourdough containing dextran synthesized by W. confusa improved the dough viscoelastic properties, and also increased the specific volume (∼21%) and reduced crumb hardness (∼12%) of the final bread, compared to control breads. Similar positive effects were not obtained with sourdough containing dextran from L. pseudomesenteroides, probably due to its higher acidity. Dextran synthesized in situ by W. confusa is a promising clean label hydrocolloid option to improve the quality of wheat bread enriched with faba bean flour. Graphical abstract: Image Highlights: Faba bean (30%) enriched wheat breads baked with and without sourdough. W. confusa -dextran increased sourdough viscosity and bread dough strength. W. confusa -dextran sourdough improved textural qualities of the composite bread. Excessive acidification had negative effect on bread volume and crumb structure.